Restrictions on Land Ownership For Citizens by States Adhering to Pancasila Ideology, Islamism and Communism - ., Bahmid; Martua, Junindra; Pratiwi, Irda (KnE Social Sciences, 2023)
Land is a necessity that cannot be separated in everyone’s life. The need for land continues to increase, but its availability is very limited. Meanwhile, the number of human growth continues to increase. So that almost all countries place land property as part of private law, but the ownership provisions are regulated by the state in public law. The focus of this research is to find out how the legal comparison of the boundaries of ownership of land rights and that of a country, by assessing the ideological values applied to a country, especially countries that adhere to Pancasila, Communism and Islamism. The aim of this research is to find the comparison of land ownership limits for every citizen who adheres to the ideology of Pancasila, Islamism and Communism, which prevails in a country. The research method used is normative legal research, which is a doctrinal research that examines the opinions of experts and legal documents or is also known as legal research. Keywords: Pancasila ideology; restrictions; Islamism; Communism; ideological values